Method for manufacturing a workpiece having a bent corner

CN123000389APending Publication Date: 2026-10-30NEW AMERIOCEAN TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611102083.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]针对上述现有技术的不足,本发明所要解决的技术问题是:提供一种具有弯角的工件制备方法以解决现有的中空薄型工件加工良率较低的问题

Benefits of technology

[0014]本发明的具有弯角的工件制备方法,至少具有如下有益效果:通过在冲压前在原料表面形成第一加强层,从而有效增加整个原料的强度,以在后续的步骤中降低甚至避免原料变形,减少冲压时弯角处形成的裂缝,同时,第一加强层厚度较低而不会影响冲压成型;第二电镀处理至少在初成型体表面形成第二加强层,不仅较好的覆盖住弯角处的裂缝,避免盐水侵蚀产生气泡,同时有效增加工件的强度和外观。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123000389A_ABST
    Figure CN123000389A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of metal processing, and discloses a workpiece preparation method with a bent corner, which comprises the following steps: S1, raw material preparation; S2, first electroplating treatment: forming a first reinforcing layer on the surface of the raw material; S3, stamping forming: stamping the raw material to form a primary forming body, the primary forming body comprising a forming part and a connecting material part connected to the forming part; S4, second electroplating treatment: forming a second reinforcing layer on the surface of the primary forming body; and S5, cleaning and blanking: removing the connecting material part to obtain the workpiece. The first reinforcing layer is formed on the surface of the raw material before stamping, thereby effectively increasing the strength of the whole raw material, reducing or even avoiding deformation of the raw material in the subsequent steps, and reducing cracks formed at the bent corner during stamping. Meanwhile, the thickness of the first reinforcing layer is low and does not affect the stamping forming. The second electroplating treatment forms the second reinforcing layer on the surface of the primary forming body, which not only better covers the cracks at the bent corner and avoids saltwater erosion to generate bubbles, but also effectively increases the strength and appearance of the workpiece.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal processing technology, and in particular to a method for preparing workpieces with bends. Background Technology

[0002] Some existing workpieces, due to design requirements, often have bends formed after bending, typically achieved through stamping. For thin, hollow workpieces with low overall strength, micro-cracks inevitably form at the bends during stamping. In subsequent salt spray testing, the salt water reacts through these cracks, causing blistering and severely impacting product quality. The traditional solution is to pre-treat the workpiece with a pre-applied strip for electroplating, thus covering the blistering area. However, because the workpiece is hollow and thin, its overall strength is too low. During electroplating, the workpiece needs to be hung on a fixture, but its strength cannot withstand the tension of the fixture, leading to severe deformation after electroplating and affecting structural assembly. Therefore, the traditional processing method results in a low yield rate for the finished workpiece. Summary of the Invention

[0003] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to provide a method for preparing workpieces with bends to solve the problem of low yield in the processing of hollow thin workpieces.

[0004] To solve the above-mentioned technical problems, one technical solution adopted by the present invention is: a method for preparing a workpiece with a bend includes the following steps: S1. Raw material preparation; S2, First electroplating treatment: forming a first reinforcing layer on the surface of the raw material; S3, stamping: a preliminary formed body is formed by stamping on a raw material having a first reinforcing layer, the preliminary formed body including a forming part and a connecting part connected to the forming part; S4. Second electroplating treatment: forming a second reinforcing layer on the surface of the initial molded body; S5. Clean up the unloaded material: Remove the connecting part to obtain the workpiece.

[0005] Furthermore, step S1 includes the following sub-steps: S11. Degreasing treatment: Use auxiliary agents to remove oil stains from the surface of the raw materials; S12, Oxide film removal treatment: Remove the oxide film from the surface of the raw material, followed by cleaning and alkali removal; S13, Zinc immersion treatment: forming a transition layer on the surface of the raw material.

[0006] Furthermore, step S11 includes the following sub-steps: S111. Use an alkaline degreasing agent to apply ultrasonic waves to the raw material for degreasing; Among them, the alkaline degreasing agent is 40-60 g / L, the ultrasonic application duration is 3-5 min, and the continuous temperature is 50-60℃; S112, and use an electrolyte to apply an electric current to the raw material for degreasing and enhanced degreasing; The electrolyte components include: sodium carbonate 30-40 g / L, sodium phosphate 20-30 g / L, and emulsifier 1-2 g / L; The applied current applies an anode current and includes a first current phase having a first current density range of 2–3 A / dm². 2 The duration is 1 to 3 minutes, and the temperature is 50 to 60°C.

[0007] Furthermore, step S12 includes the following sub-steps: S121. An alkaline solvent is used to contact the raw material to etch the oxide film on the surface of the raw material. The alkaline solvent includes 30-40 g / L NaOH, the continuous temperature is 45-50°C, and the duration is 20-40 s; S122. Neutralize the alkaline solvent remaining on the raw material with a first acidic solvent; The first acidic solvent includes 250-300 ml / L of nitric acid diluted with pure water at room temperature for 30-60 seconds.

[0008] Furthermore, step S13 includes a first zinc precipitation step and a second zinc precipitation step, in which the raw material is contacted with a zinc-containing transition liquid. The first zinc precipitation step includes contacting the raw material with a transition liquid to replace the zinc in the transition liquid to the surface of the raw material to form a thin zinc layer, washing the raw material with water, and then contacting the raw material with a second acidic solvent to dissolve the thin zinc layer, so that the surface of the raw material forms a roughened substrate surface. In the step of contacting the raw material with the transition liquid for 60-65 seconds, the second acidic solvent in the step of contacting the raw material includes 10% nitric acid and the contact time is 10-20 seconds. The second zinc deposition step includes contacting the raw material with a transition solution to form a transition layer on the surface of the raw material; The transition liquid comprises: NaOH 110-120 g / L, ZnO 8-10 g / L, sodium gluconate 30-35 g / L, nickel sulfate 2-5 g / L, and thiourea 0.5-1.0 g / L. The contact time between the transition liquid and the raw material is 30-40 seconds.

[0009] Furthermore, the first electroplating process begins within 10 seconds after step S1 is completed; In step S2, the application of electrical energy applies an anode current and includes a second current stage having a second current density range and a third current stage having a third current density range, thereby forming a first reinforcing layer on the surface of the raw material. In step S2, the continuous temperature is 50–55°C, and the second current density ranges from 2.8 to 3.1 A / dm³. 2 The duration is 30 seconds, and the third current range is 1.0–1.2 A / dm. 2 The thickness of the first reinforcing layer is 0.25–0.35 μm; The first electroplating solution comprises: nickel sulfate 90-100 g / L, nickel chloride 40-50 g / L, sodium citrate 115-120 g / L, boric acid 20-27 g / L, and wetting agent 0.1-0.4 ml / L.

[0010] Furthermore, in step S3: the connecting part includes a connecting strip surrounding the periphery of the forming part and multiple secondary strips respectively connected to the connecting strip and each corner of the forming part. The width of the secondary strip is narrower than the width of the forming part and the connecting strip, and multiple hanging holes are provided on the connecting strip.

[0011] Furthermore, step S4 includes a first electroplating stage and a second electroplating stage performed sequentially. The first electroplating stage forms a second reinforcing layer on the surface of the initial molded body, and the second electroplating stage forms a third reinforcing layer on the surface of the second reinforcing layer.

[0012] Furthermore, in the first electroplating stage step: providing a second electroplating solution to contact the initial formed body, the application of electrical energy to apply an anodic current and including a fourth current stage having a fourth current density range; The fourth current stage is maintained at a temperature of 22–28°C for 15–20 minutes, and the fourth current density ranges from 1.5 to 2.0 A / dm³. 2 The thickness of the second reinforcing layer is 4.5–5.5 μm; After the second reinforcing layer is formed, the initial molded body is soaked in an activating solution to remove the oxide film formed on the surface of the second reinforcing layer. The components include: copper sulfate 190-200 g / L, concentrated sulfuric acid 50-60 ml / L, chloride ions 60-80 mg / L, and copper acid brightener 0.3-0.5 ml / L. The activation solution includes 5% dilute sulfuric acid.

[0013] Furthermore, in the second electroplating stage step: a third electroplating solution is provided to contact the initial molded body, and the application of electrical energy applies an anodic current and includes a fifth current stage having a fifth current density range; The fifth current stage has a continuous temperature of 52–58°C and a duration of 20–25 min, the fifth current density ranges from 3.0 to 4.0 A / dm², and the thickness of the third reinforcing layer is 4.5–5.5 μm. The third electroplating solution comprises: nickel sulfate hexahydrate 240-255 g / L, nickel chloride 35-42 g / L, boric acid 36-40 g / L, semi-bright nickel leveling agent 0.5-0.7 ml / L, and low-foaming wetting agent 0.2-0.4 ml / L.

[0014] The method for preparing a workpiece with a bend in the present invention has at least the following beneficial effects: by forming a first reinforcing layer on the surface of the raw material before stamping, the strength of the entire raw material is effectively increased, so as to reduce or even avoid deformation of the raw material in subsequent steps and reduce cracks formed at the bend during stamping. At the same time, the thickness of the first reinforcing layer is low and will not affect the stamping process. The second electroplating treatment forms a second reinforcing layer on the surface of the initial formed body, which not only better covers the cracks at the bend and avoids the generation of bubbles by salt water erosion, but also effectively increases the strength and appearance of the workpiece. Attached Figure Description

[0015] The accompanying drawings, which are included to provide a further understanding of this application and form part of this application, illustrate exemplary embodiments and are used to explain this application, but do not constitute an undue limitation of this application. In the drawings: Figure 1 This is a flowchart of the method for preparing a workpiece with a curved corner according to the present invention; Figure 2 This is a schematic diagram of the raw material structure in step S1 of the workpiece preparation method with a curved corner of the present invention; Figure 3 This is a schematic diagram of the structure of the initial formed body in step S3 of the workpiece preparation method with a curved corner of the present invention; Figure 4 The workpiece obtained in step S5 of the workpiece preparation method with a bend in this invention. The meanings of the labels in the attached diagram are as follows: Raw material 1, initial shape 2, forming part 21, connecting part 22, connecting strip 221, secondary strip 222, hanging hole 223, workpiece 3, bend 31. Detailed Implementation

[0016] The invention will now be further described with reference to the accompanying drawings.

[0017] Please see Figure 1 The method for preparing the workpiece 3 with a bend angle 31 according to the present invention includes the following steps: S1, please refer to Figure 2 Prepare raw material 1.

[0018] Step S1 includes the following sub-steps: S11. Degreasing treatment: Use an auxiliary agent to remove oil stains from the surface of raw material 1.

[0019] Step S11 includes the following sub-steps: S111. Use an alkaline degreasing agent to apply ultrasonic waves to the raw material for degreasing.

[0020] In step S11, raw material 1 is first prepared. Raw material 1 is a metal material, such as a thin aluminum alloy with a thickness of 0.15mm (AL5052-H34). For ease of processing, raw material 1 is wound up, clamped on a hanger, and placed in a corresponding container. To ensure the cleanliness of raw material 1, it is degreased by applying ultrasonic waves using an alkaline degreasing agent.

[0021] Specifically, the alkaline degreasing agent is a special alkaline degreasing agent for raw material 1, such as an aluminum alloy-specific alkaline degreasing agent at a concentration of 40–60 g / L. After raw material 1 comes into contact with the alkaline degreasing agent, 40 kHz ultrasound is applied to complete the cleaning of raw material 1. The duration of ultrasound application is 3–5 minutes, and the continuous temperature is 50–60°C.

[0022] In one embodiment, an alkaline degreasing agent (or degreasing powder) at a concentration of 50 g / L is used, and ultrasonic waves at 40 kHz are applied for 3 minutes, while maintaining the temperature at 55°C, to remove stamping and stretching oil, mold release agent, and dust from the surface of raw material 1, facilitating subsequent processing. After degreasing, a water washing process is required.

[0023] S112. Apply an electric current to the raw material using an electrolyte to remove oil and enhance degreasing.

[0024] In this step, to thoroughly remove oil stains that were missed during ultrasonic cleaning, such as those in the micropores of raw material 1, an electrolyte is used and an electric current is applied to enhance degreasing and oil removal. The electrolyte components include: 30–40 g / L sodium carbonate, 20–30 g / L sodium phosphate, and 1–2 g / L emulsifier.

[0025] The applied current is applied to perform anodic electrolysis, thereby precipitating hydrogen atoms with strong reducing properties to a certain extent. This slightly reduces the extremely thin oxide film on the surface of raw material 1 (such as aluminum) and activates the surface of raw material 1. The applied current includes a first current stage with a first current density range of 2 to 3 A / dm³. 2 The process lasts for 1–3 minutes at a temperature of 50–60°C. After completion, raw material 1 must be washed with water.

[0026] In one embodiment, the electrolyte components include: 30 g / L sodium carbonate, 20 g / L sodium phosphate, and 1 g / L emulsifier; the first current density range is 3 A / dm³.2 The process lasts for 2 minutes at a constant temperature of 55°C. This effectively removes stubborn oil stains, eliminates residues in hard-to-clean areas caused by ultrasonic waves, and the gas released during electrolysis forms a dynamic bubble barrier on the surface of raw material 1, preventing free oil stains from approaching and stabilizing the oil stains in the solution, ensuring that the surface of raw material 1 is "wet and clean" after degreasing.

[0027] In another embodiment, the electrolyte components include: 33 g / L sodium carbonate, 25 g / L sodium phosphate, and 2 g / L emulsifier; the first current density range is 2 A / dm³. 2 Duration: 2 minutes, temperature: 55℃.

[0028] S12, Oxide film removal treatment: Remove the oxide film on the surface of raw material 1, and then clean and remove alkali.

[0029] Step S12 includes the following sub-steps: S121. An alkaline solvent is used to contact the raw material 1 to etch the oxide film on the surface of the raw material 1.

[0030] Specifically, the alkaline solvent includes NaOH with a concentration ranging from 30 to 40 g / L, in which raw material 1 is immersed. Since raw material 1 contains a certain amount of magnesium, and aluminum has a lower potential than magnesium, the aluminum matrix, acting as the anode, preferentially dissolves and sinks. Most of the magnesium dissolves in the aluminum matrix, with a small portion precipitating as the β phase (Al3Mg2). When the magnesium rapidly dissolves on the aluminum surface, the β phase gradually protrudes and remains on the surface due to its extremely slow dissolution rate. The magnesium reacts with water in the solution to form magnesium hydroxide, which, along with the β phase, forms a loose, gel-like, poorly conductive barrier film, hindering local dissolution. Therefore, the raw material 1 is continuously immersed in the alkaline solvent at a temperature of 45–50°C to slow down the diffusion of the β phase and inhibit the formation of magnesium hydroxide colloid. The reaction is terminated after 20–40 seconds, before a dense covering layer of magnesium hydroxide barrier film has formed and the thinning of the aluminum substrate is controllable. Following this, a rapid dilution with overflow water is performed to perfectly avoid surface roughness and obtain a pure, matte silver-white raw material 1, removing the aluminum oxide film from its surface. More preferably, an aluminum corrosion inhibitor (such as silicate or gluconate) is added to suppress the dissolution rate and control surface ash buildup during alkaline etching, thus ensuring the uniform formation of the matte silver-white raw material 1. After alkaline etching, the raw material 1 is washed with overflow water.

[0031] In one embodiment, the concentration of the alkaline solvent NaOH was 30 g / L, the alkaline etching temperature was maintained at 50°C, and the duration was 30 s.

[0032] S122. The alkaline solvent remaining on the raw material 1 is neutralized by a first acidic solvent.

[0033] To prevent alkaline residues from remaining on raw material 1 after alkaline etching and washing, a first acidic solvent is used for neutralization. Specifically, the first acidic solvent consists of 250–300 ml / L of nitric acid (industrial nitric acid) diluted with pure water at room temperature, such as 300 ml / L nitric acid. The first acidic solvent is applied for 30–60 seconds. If the duration is maintained at 30 seconds, the residual alkali on raw material 1 is neutralized, and the aluminum magnesium ash produced during the alkaline etching process is dissolved, keeping the surface of raw material 1 shiny.

[0034] S13. Zinc immersion treatment: Neutralize the alkali on the surface of raw material 1 with a neutralizing agent to roughen the surface of raw material 1 and form a transition layer on the surface of raw material 1.

[0035] Step S13 includes a first zinc precipitation step and a second zinc precipitation step, both of which involve contacting raw material 1 with a zinc-containing transition liquid.

[0036] Specifically, the transition solution components include: NaOH 110-120 g / L, ZnO 8-10 g / L, sodium gluconate 30-35 g / L, nickel sulfate 2-5 g / L, and thiourea 0.5-1.0 g / L.

[0037] In one embodiment, the concentrations of NaOH, ZnO, sodium gluconate, nickel sulfate, and thiourea are 120 g / L, 10 g / L, 35 g / L, 5 g / L, and 0.8 g / L, respectively.

[0038] In another embodiment, the concentration of NaOH is 115 g / L, the concentration of ZnO is 8 g / L, the concentration of sodium gluconate is 30 g / L, the concentration of nickel sulfate is 4 g / L, and the concentration of thiourea is 1.0 g / L.

[0039] In this step, the first zinc deposition step includes contacting raw material 1 with a transition solution, displacing the zinc in the transition solution to the surface of raw material 1 to form a thin zinc layer. After washing raw material 1 with water, a second acidic solvent is used to contact raw material 1 to dissolve the thin zinc layer, resulting in a roughened substrate surface. In the first zinc deposition step, raw material 1 is immersed in the transition solution for 60-65 seconds, allowing the transition solution to continuously dissolve and displace the surface of raw material 1, thus ensuring the formation of the thin zinc layer. In the second acidic solvent contact step, the second acidic solvent includes 10% nitric acid, and the contact time is 10-20 seconds. This dissolves the thin zinc layer in a short time. Due to the local micro-battery effect generated during the dissolution of the thin zinc layer, the second acidic solvent preferentially and slightly dissolves the aluminum substrate in raw material 1, forming a rough surface. It also neutralizes and peels off the alkaline transition solution to a certain extent, ensuring the cleanliness of the surface of raw material 1. It should be noted that the contact time of the second acidic solvent with raw material 1 should not exceed 20 seconds, otherwise the second acidic solvent may easily damage the aluminum substrate.

[0040] In one embodiment, the first zinc deposition step maintains a Baume degree of 20-22Be and a temperature of 22-28°C (room temperature). The contact time between the transition liquid and the raw material 1 is 60s. After the thin zinc layer is formed, it needs to be washed with pure water. Then, the raw material 1 is soaked in 10% nitric acid for 15s to complete the dezincification, so that the thin zinc layer is completely dissolved and the surface of the raw material 1 is roughened.

[0041] In this step, the second zinc deposition step includes contacting the raw material 1 with a transition solution, thereby forming a transition layer on the surface of the raw material 1 by displacement. Specifically, in the second zinc deposition step, since the surface of the raw material 1 has been roughened in the first zinc deposition step, after the transition solution contacts the raw material 1, dense zinc crystals are formed on the surface of the raw material 1. The contact time of the transition solution with the raw material 1 is 30-40 seconds, so as to form a light gray transition layer covering the surface of the raw material 1. After that, a short rinsing with pure water is performed, such as within 10 seconds, and then the process proceeds to the next step immediately.

[0042] S2, First Electroplating Treatment: A first electroplating solution is provided, and the raw material 1 is brought into contact with the first electroplating solution and electrical energy is applied to form a first reinforcing layer on the surface of the raw material 1. The first electroplating treatment must be initiated within 10 seconds after step S1 to prevent zinc oxidation and failure.

[0043] In this step, the first electroplating solution comprises: nickel sulfate 90–100 g / L, nickel chloride 40–50 g / L, sodium citrate 115–120 g / L, boric acid 20–27 g / L, and wetting agent 0.1–0.4 ml / L. Sodium citrate serves as a neutral buffer, maintaining the pH of the first electroplating solution at 7.0–7.3. This prevents aluminum and zinc, both amphoteric metals, from chemically dissolving or becoming trapped within the solution, maintains the stability of nickel ions, and stabilizes zinc ions released due to the trace dissolution of the transition layer, preventing zinc ions from poisoning the plating layer and causing embrittlement and cracking.

[0044] In step S2, the applied electrical energy is the application of an anodic current. The applied electrical energy includes a second current stage with a second current density range and a third current stage with a third current density range, thereby forming a first reinforcing layer on the surface of the raw material 1. The temperature range for both the second and third current stages is 50–55°C.

[0045] Specifically, the second current density ranges from 2.8 to 3.1 A / dm². 2 The second current stage lasts for 30 seconds, causing nickel ions to rapidly form a coating on the transition layer (i.e., the zinc layer). This coating is firmly embedded in the transition layer, thus forming a dense, thin nickel film in a short time. This physically isolates the zinc layer from the transition liquid, inhibits the displacement side reaction between zinc and nickel ions, and prevents the zinc layer from corroding. The third current range is 1.0–1.2 A / dm³. 2Conventional electroplating is then performed to deposit nickel on the surface of raw material 1, forming a first reinforcing layer. The current is reduced to prevent excessive stress within the first reinforcing layer from causing detachment. The thickness of the first reinforcing layer is 0.25–0.35 μm, such as 0.3 μm, thus forming a thin reinforcing layer formed by nickel ion deposition. This improves the strength of raw material 1 without affecting the stamping process, isolates the zinc layer, prevents displacement bubbles, and enhances the adhesion to the substrate.

[0046] In one embodiment, the total duration of the second and third current stages is 3 minutes, and the deposition rate is approximately 0.1 μm / min. The workpiece 3 is placed in the corresponding container, and the second current density is 3 A / dm³. 2 After 30 seconds, the current density was reduced to 1.2 A / dm². 2 .

[0047] It should be noted that the pH value needs to be tested regularly throughout the electroplating process. If the pH value is found to be outside the range, it needs to be adjusted by adding or removing ammonia and / or dilute copper sulfate.

[0048] S3, please refer to Figure 3 Stamping: A preliminary formed body 2 is formed by stamping on a raw material 1 coated with a first reinforcing layer. The preliminary formed body 2 includes a forming part 21 formed by stamping with the same structure as the workpiece 3 and a connecting part 22 connected to the forming part 21. An auxiliary area is formed between the connecting part 22 and the forming part 21 for hooking the connecting part 22 onto a hanger.

[0049] In this step, the forming part 21 is adapted to the structural stamping of the workpiece 3. In one embodiment, the forming part 21 (or workpiece 3) includes five sides and has a frame-like structure. Each side has an L-shaped cross section and is bent in the middle to form a bend 31 or angle. Multiple notches are formed on one side of each side.

[0050] In step S3, the connecting section 22 includes a connecting strip 221 surrounding the periphery of the forming section 21, and multiple secondary strips 222 respectively connected to the corners of the connecting strip 221 and the forming section 21. The width of the secondary strips 222 is narrower than the width of the forming section 21 and the connecting strip 221 to achieve connection between the forming section 21 and the connecting strip 221. Multiple hanging holes 223 are provided on the connecting strip 221 to facilitate the positioning of the initial formed body 2 by hanging it on the hanger through the hanging holes 223. Alternatively, the connecting strip 221 can be hung on the hanger through the gap between it and the forming section 21, so that the connecting strip 221 is partially supported on the hanger while the forming section 21 does not contact the hanger, thereby avoiding deformation of the forming section 21 to a certain extent in subsequent processes. For this purpose, the gap between the connecting strip 221 and the forming section 21 and the multiple hanging holes 223 can be configured as auxiliary areas.

[0051] In this embodiment, the secondary material strip 222 is S-shaped to ensure both connection and elastic support for the forming part 21, thereby providing free stretching and adjustment, making the flatness and other indicators adjustable when deviations occur; the S-shaped secondary material strip 222 can also absorb and eliminate the internal stress formed inside the material during stamping through elastic stretching and deformation; the secondary material strip 222, made of the same material as the forming part 21, can also conduct electricity in the subsequent electroplating process; due to its small cross-section, the secondary material strip 222 can better ensure the dimensional accuracy and appearance quality of the product during subsequent blanking.

[0052] S4. Second electroplating treatment: At least a second electroplating solution is provided, so that the initial molded body 2 comes into contact with the second electroplating solution and electrical energy is applied to form at least a second reinforcing layer resistant to salt water corrosion on the surface of the raw material 1.

[0053] In one embodiment, the second electroplating process includes a first electroplating stage in which the initial molded body 2 is placed in a second electroplating solution, thereby forming a second reinforcing layer on the initial molded body 2.

[0054] In another embodiment, the second electroplating process includes a first electroplating stage and a second electroplating stage performed sequentially. In the first electroplating stage, a second electroplating solution is provided and contacts the initial molded body 2, so that the first electroplating stage forms a second reinforcing layer on the surface of the initial molded body 2. Then, a third electroplating solution is provided, so that the second electroplating stage forms a third reinforcing layer on the surface of the second reinforcing layer.

[0055] In this step, the second electroplating solution comprises: 190–200 g / L copper sulfate, 50–60 ml / L concentrated sulfuric acid, 60–80 mg / L chloride ions, and an appropriate amount of copper sulfate brightener. The pH value of the second electroplating solution is controlled at 0.4–0.8, and electroplating deposition is carried out at room temperature.

[0056] In one embodiment, the second electroplating solution comprises 200 g / L copper sulfate, 55 ml / L concentrated sulfuric acid, 70 mg / L chloride ions, and 0.5 ml / L copper acid brightener A / B. The copper sulfate and concentrated sulfuric acid ensure the smoothing effect of the deposition, guaranteeing limited deposition of copper ions in microscopic depressions to achieve a filling effect. The chloride ions, in conjunction with the carrier in the copper acid brightener A / B, form a molecular sieve adsorbed onto the electrode surface, ensuring stable deposition of the coating. The chloride ions are provided using hydrochloric acid.

[0057] In another embodiment, the second electroplating solution comprises 190 g / L copper sulfate, 60 ml / L concentrated sulfuric acid, 60 mg / L chloride ions, and 0.3–0.5 ml / L copper acid brightener.

[0058] In the first electroplating stage, after the initial molded body 2 is hung on the hanger and placed in the container, the second electroplating solution is provided to contact and immerse the initial molded body 2. Applying electrical energy includes applying a fourth current stage with a fourth current density range. In the fourth current stage, a cathode current containing copper phosphorus is applied, wherein the phosphorus content is 0.04% to 0.06%. This forms a copper phosphate film on the surface of the initial molded body 2 during dissolution, thereby controlling the fourth current density range within the optimal dissolution range, promoting the rapid oxidation of primary copper to secondary copper, and ensuring that the final formed second reinforcing layer is burr-free.

[0059] Specifically, the fourth current stage is maintained at a temperature of 22–28°C for 15–20 minutes, with a current density ranging from 1.5 to 2.0 A / dm³. 2 During the electroplating deposition process, air agitation and continuous filtration are required. This includes supplying oxygen to the second electroplating solution and generating agitation to eliminate concentration polarization. Multiple filtrations can be performed using a filter inserted into the deposition container to continuously remove solid particles and some organic decomposition products from the second electroplating solution, preventing defects such as burrs and pitting in the second reinforcing layer. The final result is a second reinforcing layer formed by copper ion deposition with a thickness of 4.5–5.5 μm and a deposition rate of approximately 0.25 μm / min. In one embodiment, the fourth current stage lasts for 20 minutes, and the fourth current density is 2.0 A / dm³. 2 The second reinforcing layer has a thickness of 5 μm. This second reinforcing layer fills the fine scratches generated during the stamping process, levels the substrate, and provides an extensible base for the first reinforcing layer. After the second reinforcing layer is formed, the initial molded body 2 is cleaned using a three-stage counter-current water wash to prevent residues on the initial molded body 2 from being carried into subsequent processes and to avoid copper ion contamination of subsequent processes, which could lead to defects such as pitting and pinholes.

[0060] In this step, after the second reinforcing layer is formed, the initial molded body 2 needs to be immersed in an activating solution to remove the oxide film formed on the surface of the second reinforcing layer. Specifically, the activating solution includes 5% dilute sulfuric acid and is immersed for 15 seconds to remove the passivation film on the surface of the second reinforcing layer. Finally, it is subjected to multi-stage water washing until acid residue is completely removed to avoid corrosion of the nickel layer.

[0061] In the second electroplating stage step, a third electroplating solution is provided to contact the initial molded body 2, and the application of electrical energy applies an anodic current and includes a fifth current stage having a fifth current density range.

[0062] In this step, the third electroplating solution comprises: nickel sulfate hexahydrate 240–255 g / L, nickel chloride 35–42 g / L, boric acid 36–40 g / L, semi-bright nickel leveling agent 0.5–0.7 ml / L, and low-foaming wetting agent 0.2–0.4 ml / L. The pH of the third electroplating solution is controlled between 3.6 and 4.0 to ensure the deposition rate, and the temperature is maintained at 52–58°C to ensure the dissolution balance of the third electroplating solution. The semi-bright nickel leveling agent ensures low sulfur content and, compared to traditional sulfur-containing electroplating components, can control stress within a lower range during deposition.

[0063] In one embodiment, the third electroplating solution comprises 250 g / L nickel sulfate hexahydrate, 40 g / L nickel chloride, 40 g / L boric acid, 0.6 ml / L semi-bright nickel leveling agent, and 0.3 ml / L low-foaming wetting agent, with the temperature preferably controlled at 55°C. The pH value is adjusted by adding or subtracting dilute sulfuric acid and / or nickel carbonate. The flowing nickel sulfate and nickel chloride ensure a good anodic heat distribution and conductivity, while the boric acid at 55°C provides sufficient buffering capacity to resist localized pH increases caused by hydrogen evolution at the cathode, preventing brittle plating caused by nickel hydroxide inclusions. The semi-bright nickel leveling agent improves the substrate deposition rate, enhances adsorption in micro-depressions, and ensures a smoothing effect.

[0064] In the second electroplating stage, the preform 2 with the second reinforcing layer is hung on a fixture and placed in a corresponding container, immersing it in the third electroplating solution. In the fifth current stage, an anodic current is applied, and the nickel plate is electrolyzed, using an anodic bag for filtration. The fifth current stage is maintained at a temperature of 52–58°C for 20–25 minutes, with a current density ranging from 3.0 to 4.0 A / dm². During the electroplating deposition process, air agitation and continuous activated carbon filtration are performed simultaneously. A third reinforcing layer with a nickel ion deposition thickness of 4.5–5.5 μm is ultimately formed, with a deposition rate of approximately 0.2 μm / min. In one embodiment, the fifth current stage lasts for 25 minutes, the fourth current density is 4.0 A / dm², and the third reinforcing layer is 5 μm thick. Thus, the first and third reinforcing layers on the entire surface of the preform 2 form a multi-layered nickel layer, improving its lifespan in subsequent neutral salt spray tests. At this point, the hardness and strength of the entire preform are improved, and the thicker second and third reinforcing layers effectively cover cracked areas, preventing them from being corroded by salt water.

[0065] Finally, it undergoes multi-stage pure water rinsing, followed by nickel passivation treatment. This involves using an electrolytic sealant (20 g / L) to control the pH value between 2 and 4, maintaining a temperature range of 45–55°C for 20 seconds. Electrochemical treatment is then performed by applying an electric current to form a passivation film on the surface, providing anti-discoloration and salt spray resistance. A polymer sealant can be used to fill the micropores in the plating layer and form a protective film on the surface. Afterward, it is cleaned and hot-air dried at a temperature maintained at 60–70°C.

[0066] S5, please refer to Figure 4 Cleaning the blank: Remove the connecting part 22 to allow the workpiece 3 to be blanked and formed.

[0067] In this step, after workpiece 3 is unloaded and hung, its appearance is inspected. It is necessary to ensure that workpiece 3 has no black spots, yellowing, scratches, watermarks, scorched edges, etc., and to conduct adhesion and salt spray tests. For qualified products, packaging is completed and the product is either shipped out or put into storage.

[0068] Compared with the prior art, the preparation method of workpiece 3 with bend 31 of the present invention forms a first reinforcing layer formed by nickel deposition, a second reinforcing layer formed by copper deposition, and a third reinforcing layer formed by nickel deposition on the surface of workpiece 3 from the inside to the outside. Under this structure, the adhesion test using 3M 600 tape with a specification of 1mm pendulum does not cause it to fall off when pulled, and the corrosion resistance is shown to be ≥72h with no red rust in neutral salt spray.

Claims

1. A method for preparing a workpiece with a curved corner, characterized in that, Includes the following steps: S1. Raw material preparation; S2, First electroplating treatment: forming a first reinforcing layer on the surface of the raw material; S3, stamping: a preliminary formed body is formed by stamping on a raw material having a first reinforcing layer, the preliminary formed body including a forming part and a connecting part connected to the forming part; S4. Second electroplating treatment: forming a second reinforcing layer on the surface of the initial molded body; S5. Clean up the unloaded material: Remove the connecting part to obtain the workpiece.

2. The method for preparing a workpiece with a bend as described in claim 1, characterized in that: Step S1 includes the following sub-steps: S11. Degreasing treatment: Use auxiliary agents to remove oil stains from the surface of the raw materials; S12, Oxide film removal treatment: Remove the oxide film from the surface of the raw material, followed by cleaning and alkali removal; S13, Zinc immersion treatment: forming a transition layer on the surface of the raw material.

3. The method for preparing a workpiece with a bend as described in claim 2, characterized in that: Step S11 includes the following sub-steps: S111. Use an alkaline degreasing agent to apply ultrasonic waves to the raw material for degreasing; Among them, the alkaline degreasing agent is 40-60 g / L, the ultrasonic application duration is 3-5 min, and the continuous temperature is 50-60℃; S112, and use an electrolyte to apply an electric current to the raw material for degreasing and enhanced degreasing; The electrolyte components include: sodium carbonate 30-40 g / L, sodium phosphate 20-30 g / L, and emulsifier 1-2 g / L; The applied current applies an anode current and includes a first current phase having a first current density range of 2–3 A / dm². 2 The duration is 1 to 3 minutes, and the temperature is 50 to 60°C.

4. The method for preparing a workpiece with a bend as described in claim 2, characterized in that: Step S12 includes the following sub-steps: S121. An alkaline solvent is used to contact the raw material to etch the oxide film on the surface of the raw material. The alkaline solvent includes 30-40 g / L NaOH, the continuous temperature is 45-50°C, and the duration is 20-40 s; S122. Neutralize the alkaline solvent remaining on the raw material with a first acidic solvent; The first acidic solvent includes 250-300 ml / L of nitric acid diluted with pure water at room temperature for 30-60 seconds.

5. The method for preparing a workpiece with a bend as described in claim 2, characterized in that: Step S13 includes a first zinc precipitation step and a second zinc precipitation step, in which the raw material is contacted with a zinc-containing transition liquid. The first zinc precipitation step includes contacting the raw material with a transition liquid to replace the zinc in the transition liquid to the surface of the raw material to form a thin zinc layer, washing the raw material with water, and then contacting the raw material with a second acidic solvent to dissolve the thin zinc layer, so that the surface of the raw material forms a roughened substrate surface. In the step of contacting the raw material with the transition liquid for 60-65 seconds, the second acidic solvent in the step of contacting the raw material includes 10% nitric acid and the contact time is 10-20 seconds. The second zinc deposition step includes contacting the raw material with a transition solution to form a transition layer on the surface of the raw material; The transition liquid comprises: NaOH 110-120 g / L, ZnO 8-10 g / L, sodium gluconate 30-35 g / L, nickel sulfate 2-5 g / L, and thiourea 0.5-1.0 g / L. The contact time between the transition liquid and the raw material is 30-40 seconds.

6. The method for preparing a workpiece with a bend as described in any one of claims 2 to 5, characterized in that, The first electroplating process begins within 10 seconds after step S1 is completed. In step S2, the application of electrical energy applies an anode current and includes a second current stage having a second current density range and a third current stage having a third current density range, thereby forming a first reinforcing layer on the surface of the raw material. In step S2, the continuous temperature is 50–55°C, and the second current density ranges from 2.8 to 3.1 A / dm³. 2 The duration is 30 seconds, and the third current range is 1.0–1.2 A / dm. 2 The thickness of the first reinforcing layer is 0.25–0.35 μm; The first electroplating solution comprises: nickel sulfate 90-100 g / L, nickel chloride 40-50 g / L, sodium citrate 115-120 g / L, boric acid 20-27 g / L, and wetting agent 0.1-0.4 ml / L.

7. The method for preparing a workpiece with a bend as described in claim 1, characterized in that, In step S3: the connecting part includes a connecting strip surrounding the periphery of the forming part and multiple secondary strips respectively connected to the connecting strip and each corner of the forming part. The width of the secondary strip is narrower than the width of the forming part and the connecting strip, and multiple hanging holes are provided on the connecting strip.

8. The method for preparing a workpiece with a bend as described in claim 1, characterized in that, Step S4 includes a first electroplating stage and a second electroplating stage performed sequentially. The first electroplating stage forms a second reinforcing layer on the surface of the initial molded body, and the second electroplating stage forms a third reinforcing layer on the surface of the second reinforcing layer.

9. The method for preparing a workpiece with a bend as described in claim 8, characterized in that, In the first electroplating stage step: a second electroplating solution is provided to contact the initial molded body, and the application of electrical energy applies an anodic current and includes a fourth current stage having a fourth current density range; The fourth current stage is maintained at a temperature of 22–28°C for 15–20 minutes, and the fourth current density ranges from 1.5 to 2.0 A / dm³. 2 The thickness of the second reinforcing layer is 4.5–5.5 μm; After the second reinforcing layer is formed, the initial molded body is soaked in an activating solution to remove the oxide film formed on the surface of the second reinforcing layer. The components include: copper sulfate 190-200 g / L, concentrated sulfuric acid 50-60 ml / L, chloride ions 60-80 mg / L, and copper acid brightener 0.3-0.5 ml / L. The activation solution includes 5% dilute sulfuric acid.

10. The method for preparing a workpiece with a bend as described in claim 8, characterized in that, In the second electroplating stage step: a third electroplating solution is provided to contact the initial molded body, and the application of electrical energy applies an anodic current and includes a fifth current stage having a fifth current density range; The fifth current stage has a continuous temperature of 52–58°C and a duration of 20–25 min, the fifth current density ranges from 3.0 to 4.0 A / dm², and the thickness of the third reinforcing layer is 4.5–5.5 μm. The third electroplating solution comprises: nickel sulfate hexahydrate 240-255 g / L, nickel chloride 35-42 g / L, boric acid 36-40 g / L, semi-bright nickel leveling agent 0.5-0.7 ml / L, and low-foaming wetting agent 0.2-0.4 ml / L.